DENTAL ISSUES FOR CHILDREN WITH DOWN SYNDROME - Maria-Antonela Beldiman; Ioana Grigore; Georgiana Macovei; Cristina Iordache; Elena Luca (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study The aim of this study was to evaluate the incidence of dental issues for children with Down syndrome, for a group which included 19 children diagnosed with Down syndrome, aged between 4 and 17 years old. Material and methods The protocol was the oral health assessment by dental exam, radiological examination and questionnaires completed by parents - the questionnaires completed by parents revealed that dental hygiene was very good for 10.52% of children with Down syndrome, good for 31.57% and 57.89% were poor for these patients. Malocclusion and dento-facial anomalies were recorded in most of the children with Down syndrome. Results The results of our study shown that oral hygiene is generally weak - for more than half of patients being detected cavities in clinical exams. Conclusions Regular oral health assessment should be carried out in all children with Down syndrome, in order to early detect the dental issues that can appear to these patients.